Psychosocial and environmental determinants of physical activity in a Brazilian public university employees - ELDAF: A prospective cohort study protocol - Oliveira, Aldair J.; Lopes, Claudia S.; Maranhão Neto, Geraldo de Albuquerque; de Sousa, Gustavo Mota; Paravidino, Vitor; Rostila, Mikael; Felippe Felix Mediano, Mauro; Griep, Rosane Harter; do Vale, Wesley Souza; Frota da Rocha Morgado, Fabiane (PLOS ONE, 2022)
Background Increased physical activity levels and their determinations are essential issues worldwide. The Longitudinal Study of Physical Activity Determinants (ELDAF) aims to understand the roles of psychosocial and environmental factors in workers’ physical activity levels. Methods A prospective cohort study of non-faculty civil servants from a public university (approximately 1,200 individuals) will start in 2022 (baseline). The primary measurements will be accelerometer- and questionnaire-based physical activity, social support, social network, socioeconomic status, bereavement, job stress, body image, common mental disorders, depression, and neighborhood satisfaction. Additional measurements will include necessary sociodemographic, physical morbidity, lifestyle and anthropometric information. Participants’ places of residence will be geocoded using complete addresses. All participants will furnish written, informed consent before the beginning of the study. Pilot studies were performed to identify and correct potential problems in the data collection instruments and procedures. ELDAF will be the first cohort study conducted in Latin America to investigate physical activity and its determinants.